Elements of a Theory of Design Artefacts: a contribution to critical systems development research. PhD Thesis. - Bertelsen, Olav (DAIMI Report Series, 1998)
The thesis emphasises material mediation in design, use and research by introducing the concept of design artefacts as a unifying perspective. This concept is based on a dialectical materialist approach comprising activity theory as a general perspective (mainly Engestrøm), and specifically the notion of primary, secondary and tertiary artefacts (Wartofsky). This background is complemented with the notion of boundary objects (Star), as mediators in boundary zones. Systems development is understood as a zone where heterogeneous praxes meet to change a given praxis through the construction and introduction of new (computer) artefacts; this zone is mediated by design artefacts, which make different sense to the various praxes (boundary objects). Four main themes are addressed by the thesis: Firstly, the notion of design artefacts as an integrating perspective on systems development research and praxis, is introduced and developed. Secondly, a uniform notion of development tying use and design together, is discussed in relation to designing for development in use, and in relation to the notion of design as the transformation of artefacts. Thirdly, a pragmatic philosophy of science based on the understanding of theories as design artefacts, is proposed. Fourthly, the issue of innovation and creativity, together with the role of the individual is programmatically pointed to.